1989
DOI: 10.2165/00003495-198900372-00011
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol in the Primary Prevention of Upper Gastrointestinal Tract Haemorrhage in Patients with Cirrhosis of the Liver and Oesophageal Varices1

Abstract: on behalf of a Multicentre Study Group2 2 For participants see p. 60. A prospective. randomised. multicentre. single-blind comparison of propranolol with placebo in the primary prevention of upper gastrointestinal haemorrhage was conducted in 230 cirrhotic patients with large oesophageal varices. The dose of propranolol was progressively increased until resting heart rate was reduced by 20 to 25%. The final doses were 40mg of conventional propranolol and 160 and 320mg of long-acting propranolol daily in 22. 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
1
0
0
1
Order By: Relevance
“…Because monotherapy13 and combination treatment with nitrates9 have have failed to prove superiority, PPL is still the adequate standard treatment for any trial on primary prophylaxis of variceal bleeding. The results obtained in our standard treatment arm (PPL) are well in line with the literature: the actuarial bleeding risk after 2 years is 17.6% in the present study and 22% in the large meta‐analysis of Poynard et al8 Recent trials by Lui et al (19%),13 Garcia‐Pagan et al (17% in patients with varices > 5 mm),9 and several others25–27 also reported similar bleeding rates. In the first trial comparing VBL and PPL for primary prophylaxis,18 the actuarial bleeding risk was very high in the PPL group (40% at 18 months); this prompted criticism concerning compliance and PPL dosage 28.…”
Section: Discussionsupporting
confidence: 90%
“…Because monotherapy13 and combination treatment with nitrates9 have have failed to prove superiority, PPL is still the adequate standard treatment for any trial on primary prophylaxis of variceal bleeding. The results obtained in our standard treatment arm (PPL) are well in line with the literature: the actuarial bleeding risk after 2 years is 17.6% in the present study and 22% in the large meta‐analysis of Poynard et al8 Recent trials by Lui et al (19%),13 Garcia‐Pagan et al (17% in patients with varices > 5 mm),9 and several others25–27 also reported similar bleeding rates. In the first trial comparing VBL and PPL for primary prophylaxis,18 the actuarial bleeding risk was very high in the PPL group (40% at 18 months); this prompted criticism concerning compliance and PPL dosage 28.…”
Section: Discussionsupporting
confidence: 90%
“…В то же время в другом ретроспективном исследовании с участием 95 человек установлено отсутствие дозозависимого влияния пропранолола в дозе 80-120 мг/сут на гемодинамический ответ у пациентов с ЦП и гастроэзофагеальным варикозом. Это свидетельствует о том, что низкие дозы пропранолола ниже целевой дозы могут привести к значительному гемодинамическому ответу и гораздо более безопасны и хорошо переносимы [17].…”
Section: результаты и обсуждениеunclassified